Secure sharing scheme of sensitive data in the precision medicine system - Kim, Deukhun; Kim, Heejin; Kwak, Jin (Computers, Materials and Continua, 2020)
Numerous industries, especially the medical industry, are likely to exhibit significant developments in the future. Ever since the announcement of the precision medicine initiative by the United States in 2015, interest in the field has considerably increased. The techniques of precision medicine are employed to provide optimal treatment and medical services to patients, in addition to the prevention and management of diseases via the collection and analysis of big data related to their individual genetic characteristics, occupation, living environment, and dietary habits. As this involves the accumulation and utilization of sensitive information, such as patient history, DNA, and personal details, its implementation is difficult if the data are inaccurate, exposed, or forged, and there is also a concern for privacy, as massive amount of data are collected; hence, ensuring the security of information is essential. Therefore, it is necessary to develop methods of securely sharing sensitive data for the establishment of a precision medicine system. An authentication and data sharing scheme is presented in this study on the basis of an analysis of sensitive data. The proposed scheme securely shares sensitive data of each entity in the precision medicine system according to its architecture and data flow.
Keywords: Genetic characteristics; ITS architecture; Living environment; Medical industries; Medical services; Optimal treatment; Sensitive informations; Sharing schemes; Data sharing; Keyless signature infrastructure; Precision medicine; Sensitive data